CCDC65 mutation causes primary ciliary dyskinesia with normal ultrastructure and hyperkinetic cilia. - Amjad Horani; Steven L Brody; Thomas W Ferkol; David Shoseyov; Mollie G Wasserman; Asaf Ta-shma; Kate S Wilson; Philip V Bayly; Israel Amirav; Malena Cohen-Cymberknoh; Susan K Dutcher; Orly Elpeleg; et al. (PLoS ONE, 2013)
Primary ciliary dyskinesia (PCD) is a genetic disorder characterized by impaired ciliary function, leading to chronic sinopulmonary disease. The genetic causes of PCD are still evolving, while the diagnosis is often dependent on finding a ciliary ultrastructural abnormality and immotile cilia. Here we report a novel gene associated with PCD but without ciliary ultrastructural abnormalities evident by transmission electron microscopy, but with dyskinetic cilia beating.Genetic linkage analysis was performed in a family with a PCD subject. Gene expression was studied in Chlamydomonas reinhardtii and human airway epithelial cells, using RNA assays and immunostaining. The phenotypic effects of candidate gene mutations were determined in primary culture human tracheobronchial epithelial cells transduced with gene targeted shRNA sequences. Video-microscopy was used to evaluate cilia motion.A single novel mutation in CCDC65, which created a termination codon at position 293, was identified in a subject with typical clinical features of PCD. CCDC65, an orthologue of the Chlamydomonas nexin-dynein regulatory complex protein DRC2, was localized to the cilia of normal nasal epithelial cells but was absent in those from the proband. CCDC65 expression was up-regulated during ciliogenesis in cultured airway epithelial cells, as was DRC2 in C. reinhardtii following deflagellation. Nasal epithelial cells from the affected individual and CCDC65-specific shRNA transduced normal airway epithelial cells had stiff and dyskinetic cilia beating patterns compared to control cells. Moreover, Gas8, a nexin-dynein regulatory complex component previously identified to associate with CCDC65, was absent in airway cells from the PCD subject and CCDC65-silenced cells.Mutation in CCDC65, a nexin-dynein regulatory complex member, resulted in a frameshift mutation and PCD. The affected individual had altered cilia beating patterns, and no detectable ultrastructural defects of the ciliary axoneme, emphasizing the role of the nexin-dynein regulatory complex and the limitations of certain methods for PCD diagnosis.